PENGARUH MODEL PEMBELAJARAN DAN TEKNIK PENILAIAN PORTOFOLIO TERHADAP HASIL BELAJAR BAHASA ARAB SISWA - Arifin, Bustanil (Jurnal Evaluasi Pendidikan, 2016)
This research is aimed at discovering the effects of instruction model and assessment techniques toward Arabic language learning outcomes. The research adopted is the experimental method, while the design used is factorial 2x2 (factorial post test only design). The research was conducted in MTs. Attaqwa 10 Rawa Silam and MTs. Attaqwa 16 Teluk Pucung Bekasi. The population participated in this research were 7th grade students of MTs. Attaqwa 10 Rawa Silam and MTs. Attaqwa 16 Teluk Pucung during odd semester of the 2016/2017 academic years. Samples were selected by using simple random sample totalling of 154 people. The result of the research conducted showed that the use of TPS (Think Pair Share) learning model and Documentary Portfolio assessment techniques provided a good effect on the students’ Arabic learning outcome.